PENGGUNAAN MULTIMEDIA INTERAKTIF DALAM PENINGKATAN MOTIVASI BELAJAR AQIDAH AKHLAK - Yuslinda Yuslinda (Institut Agama Islam Negeri Palopo, 2018)
This study aims to determine the application of interactive multimedia in increasing motivation to learn aqidah morals in MTs Pondok Pesantren Darul 'Ulum Ath-Thahiriyah Paladang. The purpose of this thesis was to obtain empirical data on character motivation to learn aqidah before taught using interactive multimedia and to obtain information on whether the application of interactive multimedia can enhance learning motivation of students in MTs Pondok Pesantren Darul 'Ulum Ath-Thahiriyah.